International trade in services and domestic regulations - Delimatsis, Panagiotis (Oxford University Press, 2007)
The multilateral legal framework governing trade in services -- Barriers to trade in services -- Domestic regulations and the GATS -- Creating a horizontal necessity test for services -- Transparency and domestic regulations in services